I think the answer is 2 13/20
Or, in decimals: 1.3
1/4 time 1/4 equals a half...or you can think about it as 25 plus 25 equals 50, (1/2 of a dollar)
Answer:
4x² - x - 1
Step-by-step explanation:
(f - g)(x) = f(x) - g(x) , thus
f(x) - g(x)
= 4x² - (x + 1) ← distribute parenthesis by - 1
= 4x² - x - 1
Answer:
4x - 3y = 2
Step-by-step explanation:
First, let's review what "standard form" signifies: Ax + By = C.
Starting with y = 4/3 * x - 2/3, multiply all three terms by 3 to eliminate the fractions:
3y = 4x - 2
Next, subtract 3y from both sides:
0 = 4x - 3y - 2.
It would be nice (tho' not essential) to have the coefficient of x positive. That is why I've left 4x on the right side and subtracted 3y from both sides.
finally, add 2 to both sides, obtaining 4x - 3y = 2. This is the equation in standard form.